Carotid false aneurysm after carotid stent fracture: Report of a surgical solution. (February 2015) - Sirignano, Pasqualino; Setacci, Francesco; Galzerano, Giuseppe; de Donato, Gianmarco; Setacci, Carlo
Stent fracture has been well documented in the Literature and in the majority of cases arises from the exposition of the stent to unfavourable stresses and biomechanical forces. We report a case of carotid false aneurysm after stent placement for post-surgery restenosis. Stent fracture is a clinical reality that sometimes should be considered prior to stent deployment and may require monitoring or treatment after occurrence.